ASPEK RESIDIVIS DAN PEMBERATAN PIDANA PENCURIAN DENGAN PEMBERATAN TERHADAP TINDAK PIDANA DELIK PENCURIAN YANG DILAKUKAN OLEH DARMA SUBUR - Sumiati (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
Residual and weighting in criminal offenses for theft causes harm and suffering experienced by victims of crime, this has attracted the attention of the author to examine one of the decisions of the South Jakarta District Court Case Number 538 / Pid.B / 2017 / PN.JKT.Sel. Darma alias Subur was charged with a single indictment of violating Article 363 paragraph (1) of the 4th Criminal Code, prosecuted by the South Jakarta District Prosecutor's Public Prosecutor with a prison sentence of 2 (two) years, and terminated by a Court Judge The land of Muara Bulian with criminal penalties of 9 (nine) months. In the decision the defendant has been proven legally and convincingly guilty of committing